The Anti-DNA Antibodies: Their Specificities for Unique DNA Structures and Their Unresolved Clinical Impact—A System Criticism and a Hypothesis - Rekvig, Ole Petter (Frontiers in Immunology, 2022)
Systemic lupus erythematosus (SLE) is diagnosed and classified by criteria, or by experience, intuition and traditions, and not by scientifically well-defined etiology(ies) or pathogenicity(ies). One central criterion and diagnostic factor is founded on theoretical and analytical approaches based on our imperfect definition of the term “The anti-dsDNA antibody”. “The anti-dsDNA antibody” holds an archaic position in SLE as a unique classification criterium and pathogenic factor. In a wider sense, antibodies to unique transcriptionally active or silent DNA structures and chromatin components may have individual and profound nephritogenic impact although not considered yet – not in theoretical nor in descriptive or experimental contexts. This hypothesis is contemplated here. In this analysis, our state-of-the-art conception of these antibodies is probed and found too deficient with respect to their origin, structural DNA specificities and clinical/pathogenic impact. Discoveries of DNA structures and functions started with Miescher’s Nuclein (1871), via Chargaff, Franklin, Watson and Crick, and continues today. The discoveries have left us with a DNA helix that presents distinct structures expressing unique operations of DNA. All structures are proven immunogenic! Unique autoimmune antibodies are described against e.g. ssDNA, elongated B DNA, bent B DNA, Z DNA, cruciform DNA, or individual components of chromatin. In light of the massive scientific interest in anti-DNA antibodies over decades, it is an unexpected observation that the spectrum of DNA structures has been known for decades without being implemented in clinical immunology. This leads consequently to a critical analysis of historical and contemporary evidence-based data and of ignored and one-dimensional contexts and hypotheses: i.e. “one antibody - one disease”. In this study radical viewpoints on the impact of DNA and chromatin immunity/autoimmunity are considered and discussed in context of the pathogenesis of lupus nephritis.